First Nations Women in Northern Ontario: Health, Social, and Community Priorities - Christine Simard; Alice Sabourin; K. Amanda Maranzan (University of Western Ontario, 2011)
This article reports on data from women dwelling in First Nations communities regarding (1) baseline statistics about women’s circumstances, needs, interests, and opportunities for community engagement, and 2) information about women’s present status, experience, interest, and other questions of social, economic,and health status. Two hundred twenty-six women from 35 First Nations communities completed the survey. This paper focuses on the main findings from the survey, which fall into 4 thematic areas. Theme 1 consists of demographic information as provided by participants. Theme 2 consists of social information such as housingand education. Theme 3 includes information about participants’ top community health concerns. Theme 4 examines participants’ community involvement. Use of the survey in directing women's social policy isdiscussed.